Chemistry and Applications of Benzimidazole and Its Derivatives 2019
DOI: 10.5772/intechopen.85333
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembly of Benzimidazole Derivatives and Applications

Abstract: Herein, we focus on the chemical and physical properties of benzimidazole and its derivatives used for the synthesis of supramolecular materials. The design and modification of benzimidazole opens the scope of the diversity of structures (different sizes and morphologies) that can be built. The synthesized materials include not only small coordination complexes but also isolated crystals, metal-organic frameworks, metal-coordination polymers, smart nanocontainers, and more advanced macrostructures such as micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Moreover, the effects of anions on T m did not follow the orders commonly found in monocationic ionic liquids, and links to anion properties such as size and basicity were difficult to conclude for benzimidazolium salts. The low T m values of the [NTf 2 ] − salt relative to the Br – , [BF 4 ] − , [OTf] − , and [PF 6 ] − analogues suggested that charge diffuse anions with a large volume could disrupt the π–π stacking commonly found in benzimidazolium derivatives . In this work, we observed an increase in T m when Br – was exchanged for the larger [PF 6 ] − anion in both [(C 8 Im) 2 Py]­[A] 2 and [(C 8 BzIm) 2 Py]­[A] 2 .…”
Section: Resultsmentioning
confidence: 68%
“…Moreover, the effects of anions on T m did not follow the orders commonly found in monocationic ionic liquids, and links to anion properties such as size and basicity were difficult to conclude for benzimidazolium salts. The low T m values of the [NTf 2 ] − salt relative to the Br – , [BF 4 ] − , [OTf] − , and [PF 6 ] − analogues suggested that charge diffuse anions with a large volume could disrupt the π–π stacking commonly found in benzimidazolium derivatives . In this work, we observed an increase in T m when Br – was exchanged for the larger [PF 6 ] − anion in both [(C 8 Im) 2 Py]­[A] 2 and [(C 8 BzIm) 2 Py]­[A] 2 .…”
Section: Resultsmentioning
confidence: 68%
“…Benzimidazoles have important roles in several fields. Being an essential part of biomolecules, such as vitamin B 12 , they are widely known for their therapeutic, antimicrobial, and analgesic properties. , In the field of organic materials, hydrogen bonds can limit processability, , but they can also be a useful tool for programmed self-assembly; in recent years, there has been more interest in the use of benzimidazole derivatives for achieving self-assembled supramolecular structures. In addition, benzimidazole is a well-known N-donor ligand for the formation of coordination complexes. …”
Section: Introductionmentioning
confidence: 99%